ORGANIZATIONAL COMMUNICATION OF THE GENERAL ELECTION COMMISSION IN 2024 GENERAL ELECTION - Tirta Yasa, Muhammad; Goris Seran, Gotfridus; Hernawan, Denny; Purnamasari, Irma (Jurnal Governansi, 2024)
The spread of false informations could damage the integrity of elections, but it could be prevented through the organizational communication. Clear communication, understandable voting schedule, polling station, and essential participation steps could ensure the voters with disabilities to get access to informations without barriers. The research aimed to describe how the communication of the General Election Commission of Bogor Regency could increase the participation of voters with disabilities in the 2024 general election. Effective communication within an organization was essential to convey information successfully. Positive results such as harmonious relationships and smooth coordinations could be achieved by communicating effectively. The research used the face-to-face organizational communication theory including five dimensions, namely quality of information media, ease of access to information, information distribution, information load, and information accuracy. The research used the descriptive quantitative method. Data were collected by the survey and questionaires distributed to 91 respondents. Results of the research indicated the quality of information media having mean score 4.47 categorized as very good, the information access having mean score 4.31 categorized as very good, the information distribution having mean score 4.28 categorized as very good, the information load having mean score 3.93 categorized as good, and the information accuracy having mean score 4.26 categorized as very good. Therefore, the organizational communication generally had mean score 4.25 categorized as very good. The research recommended that the effective communication was continually conducted to increase the participation of voters with disabilities.